2001
DOI: 10.1007/s004670100688
|View full text |Cite
|
Sign up to set email alerts
|

Kidney transplantation in a girl with methylmalonic acidemia and end stage renal failure

Abstract: Methylmalonic acidemia (MMA) is an inborn error of organic acid metabolism that occurs in infancy with hypotonia, vomiting, dehydration, lethargy and failure to thrive and is biochemically characterized by metabolic ketoacidosis, hyperammonemia and sometimes hyperglycinemia. It results from deficiency of methylmalonyl-CoA mutase activity due to a defect in the mutase apoenzyme or to deficient function of one of the enzymes required for metabolism of its cofactor vitamin B12. Tubulointerstitial nephritis with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 13 publications
(12 reference statements)
0
31
0
Order By: Relevance
“…We had previously reported on the case 4 years after transplant [20]. Presently, at 10-year follow-up, her renal function and her clinical state is satisfactory.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…We had previously reported on the case 4 years after transplant [20]. Presently, at 10-year follow-up, her renal function and her clinical state is satisfactory.…”
Section: Introductionmentioning
confidence: 58%
“…Examining the reported outcomes, it is immediately apparent that renal transplant, either alone [20,40,41] or in combination [32,38,39], attains better results: all patients are alive, and in all but one the metabolic status has improved. On the contrary, of the ten solo liver transplants [18,[30][31][32][33][34][35][36][37], only two are reported uneventful, whereas two have suffered from severe metabolic disorders, one has manifested progressive neurological deficit after transplantation, one is alive with neurological deficits, two died in the postoperative period due to sepsis, and of the remaining two cases, there are no outcome data available.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Renal function may improve with optimised dietary management [9]. Renal transplantation has been undertaken in a number of patients [10], although concerns have been expressed about recurrent disease in the transplanted kidney. Transplantation is often timed to avoid the need for dialysis; in other cases, HD has been used [4].…”
Section: Discussionmentioning
confidence: 99%
“…This is also suggested by Kaplan et al (2006) and Kasahara et al (2006), who both challenge the rationale of liver transplantation. In fact, a few reports have also suggested that the benefit of either renal or combined transplantation (van't Hoff et al, 1999;Chakrapani et al, 2002;Nyhan et al, 2002;Hsui et al, 2003;Kaplan et al, 2006;Kasahara et al, 2006) is greater than that of liver transplantation alone (Van Calcar et al, 1998;Lubrano et al, 2001;Coman et al, 2006).…”
Section: Discussionmentioning
confidence: 99%